Anaphylaxis management: a survey of school and day care nurses in Lebanon - Tamar Avedissian; Gladys Honein-AbouHaidar; Nuhad Dumit; Nathalie Richa (BMJ Publishing Group, 2018)
Objective Children are at a high risk of developing allergic reactions. Since they spend lots of time at the school or day care, the odds of having an allergic event in this setting is high, hence placing the onus of properly managing their event on nurses. In Lebanon, little is known whether a standardised policy for managing allergic and anaphylactic reaction exists, leaving children unsafe and the school personnel liable. Thus, the aim of this study is to describe the current practices in the management of severe allergies and anaphylaxis by Lebanese nurses working in schools and day cares and to explore the perceived need for a protocol to manage anaphylaxis reaction.Methods A cross-sectional survey with nurses working at schools and day cares in Lebanon was conducted.Results A total of 59 school and day care nurses participated. Eighteen of the school and day care nurses reported having a written policy describing the management steps. Only 12 had witnessed an anaphylactic event. Of those, 10 reported administering an antihistamine medication orally instead of epinephrine intramuscular. Most respondents (56) believed that a standardised guideline for the management of anaphylaxis was essential, and 9 indicated being hesitant to give the epinephrine intramuscular even in the presence of a policy. Finally, 55 stated the need for training nurses in identifying and managing anaphylaxis as a must.Conclusion Currently, the management of anaphylaxis reaction in schools and day cares is suboptimal. Hence, there is a need for a standardised nursing guideline and training for nurses in these settings .